Evolution and function of red pigmentation in land plants. (7th September 2022) - Davies, Kevin M; Landi, Marco; van Klink, John W; Schwinn, Kathy E; Brummell, David A; Albert, Nick W; Chagné, David; Jibran, Rubina; Kulshrestha, Samarth; Zhou, Yanfei; Bowman, John L
Abstract: Background: Land plants commonly produce red pigmentation as a response to environmental stressors, both abiotic and biotic. The type of pigment produced varies among different land plant lineages. In the majority of species they are flavonoids, a large branch of the phenylpropanoid pathway. Flavonoids that can confer red colours include 3-hydroxyanthocyanins, 3-deoxyanthocyanins, sphagnorubins and auronidins, which are the predominant red pigments in flowering plants, ferns, mosses and liverworts, respectively. However, some flowering plants have lost the capacity for anthocyanin biosynthesis and produce nitrogen-containing betalain pigments instead. Some terrestrial algal species also produce red pigmentation as an abiotic stress response, and these include both carotenoid and phenolic pigments. Scope: In this review, we examine: which environmental triggers induce red pigmentation in non-reproductive tissues; theories on the functions of stress-induced pigmentation; the evolution of the biosynthetic pathways; and structure–function aspects of different pigment types. We also compare data on stress-induced pigmentation in land plants with those for terrestrial algae, and discuss possible explanations for the lack of red pigmentation in the hornwort lineage of land plants. Conclusions: The evidence suggests that pigment biosynthetic pathways have evolved numerous times in land plants to provide compounds that have red colour to screen damaging photosynthetically active radiation but that also have secondary functions that provide specific benefits to the particular land plant lineage.